The genus Conocephalus Thunberg (Orthoptera: Tettigoniidae: Conocephalinae) in Hainan, China with description of one new species - Shi, Fu-Ming; Wang, Ping (Zootaxa, 2015)
This paper reports four species of the genus Conocephalus from Hainan, China, including Conocephalus (Xiphidion) hainanensis sp. nov. and two new records: C. (Anisoptera) maculatus (Le Guillou, 1841) and C. (Conocephalus) bambusanus Ingrisch, 1990.